Cognitive dysfunction—an under looked avenue to promote health in incarcerated elderly population through yoga - Maity, Kalyan; Majumdar, Vijaya; Patra, Sanjib; Anand, Akshay (Frontiers in Human Neuroscience, 2025)
The correctional “ageing crisis” underlined by accelerated ageing, attributed to a prior history of poor health and lifestyle choices amongst prisoners, and other imprisonment-related factors has been associated with a global burgeoning burden of cognitive impairment in prison settings. Cognitive impairment imposes a crucial, urgent economic and medical challenge for carceral healthcare systems. Further, lack of awareness and absence of regular diagnostic screenings and lack of implementation of appropriate interventions in the prison settings worsen the scenario. Amongst the limited efficacy and reported side effects of pharmacological treatments for cognitive dysfunction, Yoga, a cost-effective and scalable intervention could provide better avenues for halting cognitive deterioration in elderly prisoners. This article presents a perspective on how the adaptation of Yoga-based regimes in carceral settings could improve the needs of people with cognitive deficits across Indian prison settings. However, we also emphasize the need to understand the essence of readiness to achieve clinical effectiveness for combating cognitive deterioration, via the implementation of well-structured Yoga based rehabilitative programs.